2019
DOI: 10.3389/fpsyg.2019.00899
|View full text |Cite|
|
Sign up to set email alerts
|

Mental Model Development in Multimedia Learning: Interrelated Effects of Emotions and Self-Monitoring

Abstract: Learners’ emotions and metacognitive self-monitoring play a crucial role in mental model development, particularly in the context of multimedia learning. However, learning-centered emotions and self-monitoring have been investigated largely without accounting for their dynamic interrelations. In this study, the effects of both learner-state variables on mental model development were investigated, by modeling their interrelations over time during a multimedia learning episode. For this, 108 undergraduate studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 92 publications
(225 reference statements)
0
16
0
2
Order By: Relevance
“…Based on Pekrun's control-value theory [25,26], achievement emotions are determined by the interaction of two components: the perceived controllability of achievement activities and their outcomes, and value appraisals of the subjective value or importance of these activities or outcomes. Academic emotions, more broadly, include achievement emotions experienced in an academic context, as well as any emotions related to (1) the instruction, (2) the study process, or (3) an exam situation [27][28][29][30][31]. These three types of situations are considered representative of the three levels of academic stress experienced by college students [25].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Based on Pekrun's control-value theory [25,26], achievement emotions are determined by the interaction of two components: the perceived controllability of achievement activities and their outcomes, and value appraisals of the subjective value or importance of these activities or outcomes. Academic emotions, more broadly, include achievement emotions experienced in an academic context, as well as any emotions related to (1) the instruction, (2) the study process, or (3) an exam situation [27][28][29][30][31]. These three types of situations are considered representative of the three levels of academic stress experienced by college students [25].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 99%
“…Recent research has supplied plentiful evidence on the role of achievement emotions in the university context [30]. Positive activating emotions (enjoyment, hope, pride) were reported to be interrelated with metacognitive monitoring processes in multimedia learning tasks, but negative emotions (frustration) and deactivating emotions (boredom) have been shown to negatively predict self-monitoring [31]. Elsewhere, the negative impact of test anxiety has been verified, and potential control mechanisms have been explored [32].…”
Section: Achievement Related Emotions As An Affective Variable Of Thementioning
confidence: 99%
“…One such factor that has been rarely considered in the aforementioned studies on emotions in digital learning environments is the co-occurrence of emotions. Even though studies have shown that the emotions outlined above have differential effects on learning depending on other affective states they are accompanied by or lead to (e.g., D’Mello and Graesser, 2012; Goetz et al, 2014; Riemer and Schrader, 2019), the co-occurrence of emotions and the breadth of emotional experiences has rarely been considered in this context.…”
Section: Introductionmentioning
confidence: 99%
“…These activity-related achievement emotions are assumed to allow for inferences about motivation and interest [ 32 , 33 ] (variables ‘enjoyment-pre’, frustration-pre’, ‘boredom-pre’). Each emotion was assessed using a single item adapted for children from Riemer and Schrader [ 52 ] (see Appendix A and Document S1b ). Moreover, children were asked about their previous experience with AR.…”
Section: Methodsmentioning
confidence: 99%
“…The children’s activity-related achievement emotions were assessed before and after the tutorial on interaction in HMD-AR using the pre-questionnaire comprises three items adapted for children from Riemer and Schrader [ 52 ] (see Figure A1 ). As explained in Section 2.3 ., pre-studies for the development of the questionnaires had shown that the children rated positive emotions as high as possible on the scale and negative emotions as low as possible on the questionnaire before and after the tutorial.…”
Section: Table A1mentioning
confidence: 99%